Calcaneal shape variation in humans, nonhuman primates, and early hominins. Issue 159 (October 2021) - Harper, Christine M.; Ruff, Christopher B.; Sylvester, Adam D.
Abstract: The foot has played a prominent role in evaluating early hominin locomotion. The calcaneus, in particular, plays an important role in weight-bearing. Although the calcanei of early hominins have been previously scrutinized, a three-dimensional analysis of the entire calcaneal shape has not been conducted. Here, we investigate the relationship between external calcaneal shape and locomotion in modern Homo sapiens ( n  = 130), Gorilla ( n  = 86), Pan ( n  = 112), Pongo ( n  = 31), Papio ( n  = 28), and hylobatids ( Hylobates, Symphalangus ; n  = 32). We use these results to place the calcanei attributed to Australopithecus sediba, A. africanus, A. afarensis, H. naledi, and Homo habilis/Paranthropus boisei into a locomotor context. Calcanei were scanned using either surface scanning or micro-CT and their external shape analyzed using a three-dimensional geometric morphometric sliding semilandmark analysis. Blomberg's K statistic was used to estimate phylogenetic signal in the shape data. Shape variation was summarized using a principal components analysis. Procrustes distances between all taxa as well as distances between each fossil and the average of each taxon were calculated. Blomberg's K statistic was small (K = 0.1651), indicating weak phylogenetic effects, suggesting variation is driven by factors other than phylogeny (e.g., locomotion or body size). Modern humans have a large calcaneus relative to body size and display a uniquely convex cuboid facet, facilitating a rigid midfoot for bipedalism. More arboreal great apes display relatively deeper cuboid facet pivot regions for increased midfoot mobility. Australopithecus afarensis demonstrates the most human-like calcaneus, consistent with obligate bipedalism. Homo naledi is primarily modern human-like, but with some intermediate traits, suggesting a different form of bipedalism than modern humans. Australopithecus africanus, A. sediba, and H. habilis/P. boisei calcanei all possess unique combinations of human and nonhuman ape-like morphologies, suggesting a combination of bipedal and arboreal behaviors.